Pengaruh Profitabilitas Dan Likuiditas Terhadap Harga Saham Sebelum Dan Saat Pandemi Covid-19 - Tri Marlina; Resti Fitria Nur Anggraini; Rachmawaty Rachman (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Financial ratios are one of the indicators used to assess the company's financial performance. The better the financial performance of a company will attract investors to invest in the company and the stock price will increase. The research aims to determine the impact of profitability as proxied by Return On Assets and Net Profit Margin, and liquidity proxied by Current Ratio and Quick Ratio on stock prices partially or simultaneously before and during the covid-19 pandemic, as well as knowing the differences in the Return On Assets, Net Profit Margin, Current Ratio, Quick Ratio, and stock prices before and during the covid-19 pandemic. This type of research is quantitative with an associative and comparative approach. The population of this research is the pharmaceutical industry sector and the Food and Beverage industry sector listed on the Indonesia Stock Exchange totaling 43 companies. The sampling method using purposive sampling method obtained as many as 13 companies. This research uses secondary data with data sources in the form of financial statements and stock prices for the 2019-2020 quarter from the www.idx.com website. So that the data obtained amounted to 52 data. In this research, in testing the data using IBM SPSS ver 25, the data analysis was carried out by multiple linear regression analysis and also different tests, namely the paired sample t-test and the Wilcoxon signed rank test. The results obtained are that partially ROA and CR have no significant effect on stock prices before and during the covid-19 pandemic, while NPM and QR have a significant effect on stock prices before and during the covid-19 pandemic. Simultaneously ROA, NPM, CR and QR have an effect on stock prices before and during the covid-19 pandemic. There is no difference between ROA, NPM, and Stock Price between before and during covid-19, while CR and QR there is a difference between before and during the covid-19 pandemic. The calculation of the coefficient of determination before covid-19 pandemic showed that all independent variables could explain the dependent variable of 81.1% and the remaining 18.9% was explained by factors outside the study, while during covid-19 pandemic all independent variables could explain the dependent variable of 21.8% the remaining 78.2% is explained by factors outside the study. Keywords: Return on Asset (ROA), Net Profit Margin (NPM), Current Ratio (CR). Quick Ratio (QR), Stock Price